Endobronchial Electrocautery Using Snare. Issue 4 (1996) - Kawahara, Masaaki; Furuse, Kiyoyuki; Kodama, Nagahisa; Ogawara, Mitsumasa; Atagi, Shinji; Kamimori, Takao; Nakao, Mitsunobu; Naka, Nobuyuki
Abstract : Between May 1987 and March 1994, upper airway and tracheobronchial electrosurgery with snare was performed in 13 patients (10 men and 3 women), ranging in age from 18 to 87 years. Four patients had benign lesions, and nine had malignant tumors. Total eradication has been achieved in the two patients with benign lesions. Electroexcision of the endobronchial portion of the tumor helped to clear the respiratory airways in all cases with malignant tumors. There has been no major side effects such as bleeding due to this method. Electrocautery is an available economical tool, which helps to diagnose and treat obstructing airway mass lesions.